2017
DOI: 10.22478/ufpb.1981-1268.2017v11n4.35466
|View full text |Cite
|
Sign up to set email alerts
|

O Aumento da Temperatura Reduz a Tolerância ao Estresse Hídrico na Germinação de Sementes de Pereskia grandifolia Haw. subsp. grandifolia (Cactaceae)?

Abstract: O objetivo deste estudo foi avaliar se o aumento da temperatura reduz a tolerância ao estresse hídrico na germinação de sementes de Pereskia grandifolia Haw. subsp. grandifolia (Cactaceae). O déficit hídrico foi simulado com soluções de polietilenoglicol 6000 nos potenciais osmóticos de 0,0; -0,1; -0,3; -0,6 e -0,9 MPa e as temperaturas constantes avaliadas foram as de 25 e 30°C. Os dados de frequência da germinação de sementes indicaram diferenças no comportamento germinativo entre as temperaturas de 25 e 30°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
7
0
2
Order By: Relevance
“…In addition, in the species where the effect of water potential and temperature has been combined, normally at 25 °C, better results have been obtained than at temperatures of 30 °C or higher (Oliveira et al 2017. For primarily arid and semiarid species with small seeds, as occurs in Cactaceae, the preference for germinating in humid soil can be an advantage that permits to reduce seedling mortality when faced with transient rain followed by prolonged droughts.…”
Section: Seed Dormancy Rojas-aréchiga and Vázquez-yanesmentioning
confidence: 99%
“…In addition, in the species where the effect of water potential and temperature has been combined, normally at 25 °C, better results have been obtained than at temperatures of 30 °C or higher (Oliveira et al 2017. For primarily arid and semiarid species with small seeds, as occurs in Cactaceae, the preference for germinating in humid soil can be an advantage that permits to reduce seedling mortality when faced with transient rain followed by prolonged droughts.…”
Section: Seed Dormancy Rojas-aréchiga and Vázquez-yanesmentioning
confidence: 99%
“…During the evaluation of whether increased temperature reduces water stress tolerance in the germination of Pereskia grandifolia Haw. (Cactaceae) seeds while using polyethylene glycol (PEG 6000) to simulate the water deficit, Oliveira et al (2017) found a decrease in seed germination rate with the osmotic potential reduction, regardless of the evaluated temperature. However, the increased temperature reduced the water stress tolerance in the germination of P. grandifolia seeds.…”
Section: Resultsmentioning
confidence: 94%
“…Irwin & Barneby (Fabaceae) . Each species germinates at a specific critical osmotic potential (Oliveira et al 2017). In addition, the environmental conditions from which the seeds were produced may influence the physiological responses to the abiotic conditions present during the germination of these seeds (Lima and Meiado 2017).…”
Section: Discussionmentioning
confidence: 99%